Trans-Renal Cell-Free Tumor DNA for Urine-Based Liquid Biopsy of Cancer - Dermody, Sarah M.; Bhambhani, Chandan; Swiecicki, Paul L.; Brenner, J. Chad; Tewari, Muneesh (Frontiers in Genetics, 2022)
Cancer biomarkers are a promising tool for cancer detection, personalization of therapy, and monitoring of treatment response or recurrence. “Liquid biopsy” commonly refers to minimally invasive or non-invasive sampling of a bodily fluid (i.e. blood, urine, saliva) for detection of cancer biomarkers such as circulating tumor cells or cell-free tumor DNA (ctDNA). These methods offer a means to collect frequent tumor assessments without needing surgical biopsies. Despite much progress with blood-based liquid biopsy approaches, there are limitations, including the limited amount of blood that can be drawn from a person and challenges with collecting blood samples at frequent intervals to capture ctDNA biomarker kinetics. These limitations are important because ctDNA is present at extremely low levels in plasma and there is evidence that measuring ctDNA biomarker kinetics over time can be useful for clinical prediction. Additionally, blood-based assays require access to trained phlebotomists and often a trip to a healthcare facility. In contrast, urine is a body fluid that can be self-collected from a patient’s home, including at frequent intervals, and mailed to a laboratory for analysis. Multiple reports indicate that fragments of ctDNA pass from the bloodstream through the kidney’s glomerular filtration system into the urine, where they are known as trans-renal ctDNA (TR-ctDNA). Accumulating studies indicate that the limitations of blood based ctDNA approaches for cancer can be overcome by measuring TR-ctDNA. Here, we review current knowledge about TR-ctDNA in urine as a cancer biomarker approach, and discuss its clinical potential and open questions in this research field.